Analysis of shoreline changes in the city of Gorontalo using remote sensing technology - Mahua, Musdalifah H.; Kasim, Faizal; Pasisingi, Nuralim (Universitas Malikussaleh, 2024)
Coastal areas are essential for economic activities but are also vulnerable to environmental changes caused by human activities. Remote sensing technology can help monitor shoreline changes efficiently and accurately related to the spatial-temporal dynamics of the local area's coastline, which is needed to develop an effective coastal management strategy. By using the Modified Normalized Difference Water Index (MNDWI) water index method for shoreline extraction, the results show that the addition of coastal areas (accretion) as part of the dominant process for coastal equilibrium in almost all coastal regions in Gorontalo City during the 2000-2022 period, experienced trend acceleration significantly during the 2015-2022 period with an increase in the accretion rate of 60.15%. The accretion rate in this period has resulted in an increase in the land area of the coastal zone by 425.44% compared to the accretion that occurred during the 2000-2015 period. The findings of this study can be used as a basis for further research regarding the impact of human activities on coastal ecosystems and the effectiveness of coastal management strategies for Gorontalo City.Keywords: Google earth engine; coastal equilibrium; landsat; sentinel-2; MNDWI